PERENCANAAN KARIER SISWA DI SMA DITINJAU DARI STATUS SOSIAL EKONOMI, JENIS KELAMIN, DAN JURUSAN - Sulusyawati, Heni; Yusuf, A. Muri; Daharnis, Daharnis (Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2017)
The background of this research was motivated by there were students who have not the goal and a clear career plan. The purpose of this study were (1) describe students career planning is sighted socio-economic status, gender, and majors, (2) examined differences in students career planning of socio-economic status of high, medium, and low, (3) examined differences in students career planning of based on male and female, (4) examined differences in students career planning majoring in science and social studies, (5) examined differences in career planning of students based on interaction of between socio-economic status, gender, and majors. This research is a comparative descriptive study using 2 x 2 x 3 factorial design. The population of this research was a class XI students at SMAN 7 Padang with 258 students. Sample this research consistsof 160 people and selected by proportional random sampling technique. The instrument was using career planning scale reliability value of 0,751. Data were analyzed using descriptive statistics and Analysis of Variance (ANOVA). The results showed that: (1) students career planning in terms of socio-economic status, gender, and majors at the high category, (2) there is no significant differences in career planning ofstudents in terms of socio-economic status of high, medium and low, (3) there is no significant differences in career planning of students in terms of male and female, (4) there is nosignificant difference in career planning of students in terms of majoring in science and social studies, (5) there is no difference in career planning of students in terms of interaction between socio-economic status, gender, and majors. The implication of this research as one of an input for designing aguidance and counseling program, especially in the career planning.